A simple method for HPLC retention time prediction: linear calibration using two reference substances - Lei Sun; Hong-yu Jin; Run-tao Tian; Ming-juan Wang; Li-na Liu; Liu-ping Ye; Tian-tian Zuo; Shuang-cheng Ma (BMC, 2017)
Abstract Background Analysis of related substances in pharmaceutical chemicals and multi-components in traditional Chinese medicines needs bulk of reference substances to identify the chromatographic peaks accurately. But the reference substances are costly. Thus, the relative retention (RR) method has been widely adopted in pharmacopoeias and literatures for characterizing HPLC behaviors of those reference substances unavailable. The problem is it is difficult to reproduce the RR on different columns due to the error between measured retention time (tR) and predicted tR in some cases. Therefore, it is useful to develop an alternative and simple method for prediction of tR accurately. Methods In the present study, based on the thermodynamic theory of HPLC, a method named linear calibration using two reference substances (LCTRS) was proposed. The method includes three steps, procedure of two points prediction, procedure of validation by multiple points regression and sequential matching. The tR of compounds on a HPLC column can be calculated by standard retention time and linear relationship. Results The method was validated in two medicines on 30 columns. Conclusion It was demonstrated that, LCTRS method is simple, but more accurate and more robust on different HPLC columns than RR method. Hence quality standards using LCTRS method are easy to reproduce in different laboratories with lower cost of reference substances.